Young Workers of Industrial Enterprises: Recruitment, Adaptation, Integration - ЖидковаЕлена Михайловна (Journal of Economic Sociology, 2010)
The paper deals with the young workers of the enterprises. The subject of the survey – youth policy directed to the attraction, keeping and adaptation of young employees. The stimulating measures and integration mechanisms of young employees are under focus. The paper was prepared on the basis of the project “Management and labour relations at contemporary Russian enterprises”, which was done in 2002-2006 by ISITO with collaboration of the Centre of comparative labour surveys of Warwick University (Great Britain).